Identification of tumor nodule in soft tissue: An inverse finite‐element framework based on mechanical characterization. (15th June 2020) - Candito, Antonio; Palacio‐Torralba, Javier; Jiménez‐Aguilar, Elizabeth; Good, Daniel W.; McNeill, Alan; Reuben, Robert L.; Chen, Yuhang
Abstract: Identification and characterization of nodules in soft tissue, including their size, shape, and location, provide a basis for tumor identification. This study proposes an inverse finite‐element (FE) based computational framework, for characterizing the size of examined tissue sample and detecting the presence of embedded tumor nodules using instrumented palpation, without a priori anatomical knowledge. The inverse analysis was applied to a model system, the human prostate, and was based on the reaction forces which can be obtained by trans‐rectal mechanical probing and those from an equivalent FE model, which was optimized iteratively, by minimizing an error function between the two cases, toward the target solution. The tumor nodule can be identified through its influence on the stress state of the prostate. The effectiveness of the proposed method was further verified using a realistic prostate model reconstructed from magnetic resonance (MR) images. The results show the proposed framework to be capable of characterizing the key geometrical indices of the prostate and identifying the presence of cancerous nodules. Therefore, it has potential, when combined with instrumented palpation, for primary diagnosis of prostate cancer, and, potentially, solid tumors in other types of soft tissue. Abstract : This study proposes an inverse finite‐element based framework, for characterizing the size of examined tissue sample and detecting presence of embedded tumor nodule, without a priori anatomical knowledge. The inverse analysis was applied to human prostate, based on the reaction forces obtained by mechanical probing and those from an equivalent FE model, which was optimized iteratively toward the target. The effectiveness of the method was further verified using a realistic prostate model reconstructed from magnetic resonance (MR) images.